Effect of physical form and washing of treated and untreated rice straw with sodium hydroxide upon chemical composition and in vitro digestibility - Baghdad Science Journal (مجلة بغداد للعلوم)
Hydroxide upon the chemical composition and dry matter(DM) and organic matter(OM) digestibility . Rice straw was treated with 4% sodium hydroxide using 30% of DM basis moisture, and incubated at 40 ºC for 40 days., DM digestibility (DMD) was significantly affected (P